Freedom of Speech di Ruang Virtual: Analisis Wacana Fairclough Pada Kanal Youtube Rocky Gerung Official - Permana, Restiawan; Trikusumaningtias, Intan; Adinugroho, Prasetyo (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
New media is a communication channel that brings about change by disseminating information through texts published by authors. Because text is a form of ideological practice, language, style, word choice, and grammatical structure, it is understood as a decision that has a certain ideological meaning in order to gain public support. This research aims to analyze Rocky Gerung's freedom of speech on the Rocky Gerung Official YouTube channel and how discourse practices take place on YouTube as a virtual space. This research was carried out to examine virtual media. Using a critical paradigm, this research is descriptive-qualitative using critical discourse analysis methods. Using Norman Fairclough's thinking, at the macro-level analysis, there are linguistic elements used that are philosophical, straightforward, and rich in meaning using metaphors. At the micro level, there is the use of special terminology in the world of politics, government, and philosophy. As well as using intertextual patterns, there is consistency between one sentence and another. At the meso level of analysis, researchers create relationships between characters or participants involved in the text in this research.